Blistered and Bleeding, Tired and Determined: Visual Representations of Children and Youth in the Miles for Millions Walkathon - Myers, Tamara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2011)
This article examines images of children and youth taken in connection with the Miles for Millions walkathon, a wildly popular charity event in 1960s and 70s Canada. It argues that as cultural objects, images of children accomplished several things: they delivered potent messages about the country’s present and future, mobilized adults around Canada’s relatively new role in international development, and reassured the nation that the kids were all right. Images of Canadian youth were used alongside those of the sentimentalized, racialized Third World child, a juxtaposition that ultimately helped spark enthusiasm for the walkathon and engender a consciousness among Canadian youth of their own able-bodiedness. The visual culture of the Miles for Millions provides an excellent example of the ‘knowing child’ and of the popular contemporary style of representing children ‘in their own worlds.’ While focused on the semiotics of the Miles for Millions pictorial, this article also explores the possibility of reading the images of youth for what they can tell us about the social history of the event.